Tinjauan Yuridis Pertimbangan Hakim Menjatuhkan Pidana Penjara dan Pelatihan Kerja Terhadap Anak Sebagai Pelaku Tindak Pidana Persetubuhan (Studi Putusan Pengadilan Negeri Medan Nomor 70/Pid.Sus-Anak/2024/PN Mdn) - Risyadha, Angelica Kumala; Siregar, Fitri Yanni Dewi (Universitas Medan Area, 2025)
This study analyzes judicial considerations in sentencing imprisonment and work training for a juvenile offender in a sexual intercourse case, using the Medan District Court Verdict No. 70/Pid.Sus-Anak/2024/PN Mdn as a case study. The research is grounded in the tension between retributive justice and the principle of restorative justice within Indonesia’s juvenile criminal justice system. A normative juridical method with a case study approach is employed, examining primary, secondary, and tertiary legal materials through literature review and descriptive-analytical analysis. The findings reveal that judicial considerations include legal aspects such as the Juvenile Criminal Justice System Act (UU SPPA) and the Criminal Code (KUHP), as well as non-legal aspects like the juvenile's age, social environment, and the psychological impact on the victim. The court’s decision combines retributive, restorative, substantive, and procedural justice, reflecting a holistic approach to child protection. The study concludes that achieving a balance between punishment and rehabilitation is essential for ensuring the rights of both juvenile offenders and victims, and for delivering justice that is fair and humane.